Mensuração do desempenho de obras da construção civil quanto aos critérios de tempo e custos - Costa, Luiza Sangoi Dias da (2022)
Civil construction proves to be one of the most important global economy sectors, and its development level often indicates the country's prosperity degree. However, the sector productivity has not kept up with its growth, which is evidenced by the data on delays and extra costs in Brazilian civil construction works. In light of this problematic, the present study is inserted, whose main objective is to measure the performance regarding time and cost criteria of civil construction works in Brazil. As for the method, it is classified as applied, exploratory, and adopted the qualitative approach, by means of a Systematic Literature Review (SRL), and quantitative, by means of a survey, with the application of a structured questionnaire. Regarding the RSL, a research protocol was defined and, by means of frequency analysis and the calculation of the importance index, the 10 main causes of delays and extra costs reported in international studies conducted in the last 10 years were compiled into rankings. Regarding the survey, more than 15.000 questionnaires were applied; among these, 100 questionnaires were answered by Brazilian construction companies that performed construction works in the last 5 years. For the analysis of the survey results, descriptive, correspondence, and factor analyses were performed. As for the main results, the RSL highlights that the causes of delays and extra costs were centered on the internal environment of the companies, mainly on organizational, financial and contractual issues. Regarding the survey, the evidence shows that the construction works presented an average of 6.52% of cost overruns and 21.26% of schedule overruns. Among the variables that presented some association with the overruns, the methodologies chosen for budgeting and planning can be mentioned, in the case of extra costs, and the estimated length and size of the works, in relation to delays. Through the exploratory factor analysis it was possible to extract new latent variables entitled: problems in the pre-hiring phase; problems in hiring suppliers; problems in supply management, planning problems, and construction management problems. Based on these results, a framework was developed to improve and measure the organizational performance of civil construction works, which proposed, among other suggestions, greater attention to schedules for works of up to 750 square meters, as well as location-based planning with balance lines, and the preparation of detailed budgets.